The UK, interrogation and Iraq, 2003–2008. (3rd July 2016) - Newbery, Samantha
Abstract: The UK's interrogation operations during the conflict in Iraq (2003–2008) are often portrayed by the media as involving significant amounts of mistreatment. This article demonstrates that these practices are not necessarily representative of the UK's interrogation operations across this conflict. In doing so it contributes to the limited literature on the practice of interrogation and on the UK's combat operations in Iraq. The UK's interrogation capability, and therefore its intelligence-gathering capability, is shown to have rested primarily with the military's Joint Forward Interrogation Team (JFIT). The JFIT suffered from limitations to the number, training and experience of its interrogators and interpreters. It is argued that maintaining a permanent, higher level of preparedness for interrogation by the British armed forces is desirable.